Strategies for Enhancing Security Resilience of New Power Systems Enabled by Digital Technology - Xiaohong Chen; Gaonan Zhang; Cheng Zhang; Jiaolong Chen; Jian Guan; Zehong Liu; Zhaocheng Liu (中国工程科学)
Constructing a new power system is crucial for strengthening energy security and achieving the carbon peaking and carbon neutralization goals in China. Improving the security resilience is the core of the safe and stable development of the system, which requires the digital technology that could play a key enabling role. This study analyzes the implications and characteristics regarding the security resilience of new power systems, and sorts out the challenges faced by the improvement in security resilience, including frequent extreme events, complex system structure, and multi-energy coordination conflicts. This study expounds on the enabling effect of the digital technology on the improvement in security resilience of new power systems, summarizes the major problems existing in the enabling process, and further proposes a key technology system for improving the security resilience of new power systems through the digital technology, involving multimodal data fusion technology based on artificial intelligence, intelligent situation awareness and early-warning technology based on cloud-edge collaboration, multi-energy collaborative optimization and control technology based on big data analysis, and post-disaster emergency decision-making technology based on digital twins. To provide theoretical support for the development of new power systems, this study proposes the following suggestions: (1) emphasizing the top-level design of major projects regarding climate resilience, (2) strengthening the research and development of key digital and power technologies, (3) building data infrastructure while improving the quality assurance mechanism, and (4) optimizing the construction of a compound talent echelon in the power industry.